Innovative Method of Traction in a Bilateral Diaphyseal Femur Fracture in a Polytrauma Below-Knee Amputee - Stefan Mitrasinovic; Georgios Kiziridis; Shauni Wellekens; Charline Roslee; Syed Neshat Anjum (Case Reports in Orthopedics)
While diaphyseal femoral shaft fractures are common, it is uncommon to see this injury in leg amputees. Traditionally, these fractures are internally fixed using a fracture table with reduction obtained by traction and adequate rotation exerted on a slightly abducted extremity. Special considerations need to be given in the management of patients with leg amputations. We report the case of a 24-year-old gentleman with bilateral diaphyseal femoral shaft fractures and a previous right below-knee amputation, who was transferred to our centre following a road traffic collision. We highlight important planning that needs to be undertaken for appropriate positioning, ease of reduction, and fracture fixation. We have reviewed the literature to highlight the methods that have been previously described and our use of skeletal traction through the amputation stump that can be utilised by other surgeons in challenging situations like this.